Analysis of the Influence of Leadership, Motivation, and Work Environment on Employee Performance of PT. Zahara Jaya Mulia - Shakila Zhuhrinanda; Soulthan Saladin Batubara; Fitra Arlina Nasution (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of leadership, motivation, and work environment on employee performance at PT. Zahara Jaya Mulia. The research employed a quantitative approach with a total sample of 40 employees. Data were collected using a questionnaire, and the analysis was carried out through multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results indicate that: (1) leadership has a positive and significant effect on employee performance; (2) motivation has a positive and significant effect; (3) the work environment also has a positive and significant effect; and (4) simultaneously, the three independent variables contribute significantly to employee performance. The contribution of the independent variables to the dependent variable is relatively strong, as reflected in the R² value of 0.388. The practical implication of this study is that the company needs to enhance leadership quality, improve work motivation through an effective reward system, and create a more conducive work environment in order to improve employee performance.